Assessment of the periodontal conditions and treatment needs of adolescents and adults living in public institution homes in Metro Manila using community periodontal index of treatment needs (CPITN) - Ferrer, Jennifer
A total of 110 subjects aging 16-19,30-44,and 65-74 were examined utilizing CPITN. Calculus prevailed as the most frequently recorded score followed by deep pockets and shallow pockets respectively. Bleeding alone as a score was not seen. They are usually related to other scores like calculus and pockets. There were no healthy sextants among the subjects examined and missing sextants were uncommon except in the 65-74 age category. The treatment needs were predominantly Type 1 followed by Type II. Type III was relatively uncommon.